Kearifan Lokal Dalam Pengelolaan Padi Sebagai Strategi Kemandirian Pangan Masyarakat Adat Baduy - Mas Adi Chandra Damamora; Aris Supriyo Wibowo; Siti Widiati; Mirajiani Mirajiani; Tatang Sutisna (AGRIBIOS, 2026)
This study aims to analyze the role of local wisdom in managing rice commodities to achieve food self-sufficiency in the Baduy Indigenous community and its relevance to the Sustainable Development Goals (SDGs). The study employed a qualitative descriptive approach supported by simple quantitative analysis through the calculation of the Food Self-Sufficiency Index (KP). The research was conducted in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province using purposive sampling of five respondents representing Inner and Outer Baduy farmers. Data were collected through interviews, observation, and documentation. The results show that the huma farming system combined with rice storage in traditional granaries (leuit) is able to maintain household food availability sustainably. The average rice production reached 510 kg per household per year, while average consumption was 444 kg per year, resulting in a Food Self-Sufficiency Index of 1.13 indicating surplus conditions. The huma–leuit system reflects local wisdom that maintains ecological balance while strengthening community food security. These practices are aligned with SDGs 2 (Zero Hunger), SDGs 12 (Responsible Consumption and Production), and SDGs 15 (Life on Land).